DEVELOPING TOLERANCE IN EARLY CHILDHOOD AND IN THE MINDS OF PRE-SCHOOL CHILDREN - Turdieva Mokhira Juraqulovna (Scholar Express Journal, 2024)
In this article, one of the modern and actual problems is the concept of tolerance, its formation, religious and educational tolerance, high thinking, principles of spiritual, cultural, ideological, humanitarian tolerance, the formation of humanitarian qualities in children of primary and preschool age and ways of education are discussed.
Keywords: religious tolerance; thinking; children